Culturally grounded student engagement in global citizenship education in Philippine higher education - Airyn M. Arbuliente; Erwin B. Berry; Alvin O. Cayogyog; El Dixon G. Plazo (International Journal of Evaluation and Research in Education (IJERE), 2026)
Global citizenship education (GCE) is increasingly integrated into higher education; however, student engagement remains limited, often characterized by superficial participation rather than meaningful involvement. This study addresses this gap by examining how students experience engagement in GCE within a developing-country context. Using an interpretive phenomenological approach, data were collected from 25 undergraduate students in a Philippine state college through in-depth interviews and analyzed using interpretive phenomenological analysis (IPA). The findings reveal that engagement becomes meaningful when students participate in authentic community-based activities, develop emotional connections to real-world issues, engage in critical reflection on complex systems, and exercise voice and initiative in learning. Importantly, the study identifies culturally grounded engagement as a key dimension, showing that Filipino values such as bayanihan (communal unity), pakikipagkapwa-tao (shared humanity), and malasakit (profound care) function as resources that shape how students interpret and engage with global issues. These findings suggest that engagement in GCE is not only multidimensional but also culturally embedded. The study contributes to the literature by extending existing student engagement frameworks to incorporate cultural context as a core dimension. Practically, it highlights the need for culturally responsive and experiential pedagogies to enhance meaningful engagement in higher education.